TINJAUAN HUKUM EKONOMI SYARIAH TENTANG BEBAN BIAYA DALAM PEMBIAYAAN MIKRO DENGAN AKAD MUSYARAKAH MUTANAQISHAH DI BRI SYARIAH - Sariningsih, Sariningsih; Jaenudin, Jaenudin; Badriyah, Mila (Al-Muamalat: Jurnal Ekonomi Syariah, 2020)
The musyÄrakah mutanÄqiá¹£hah contract on micro financing in BRISyariah KCP Majalaya incurs costs (administrative fees, notary fees and insurance costs) that must be borne by the customer. This differs from the DSN MUI fatwa No.73/DSN-MUI/XI/2008 concerning MusyÄrakah MutanÄqiá¹£hah. This study aims to determine the micro financing in BRISyariah KCP Majalaya, the mechanism and its relevance to the fatwa of DSN MUI No.73/DSN-MUI/XI/2008. The method used is descriptive, which is describing microfinancing with the musyÄrakah mutanÄqiá¹£hah contract in BRISyariah KCP Majalaya. Based on the results of the study, it can be concluded that microfinance with the musyÄrakah mutanÄqiá¹£hah contract is one of the products and services provided by BRISyariah KCP Majalaya. The mechanism starts with the customer submitting an application, before the disbursement the customer must pay the full cost, the customer then shares the profit accompanied by the purchase of a portion of the bank. The cost burden in conducting microfinance with the musyÄrakah mutanÄqiá¹£hah contract is not yet relevant to the DSN MUI fatwa No.73/DSN-MUI/XI/2008, because all costs that should be borne jointly are borne by the customer, this can lead to injustice.